2018
DOI: 10.3390/ma11040558
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prolonged Silver Nanoparticle Exposure on the Contextual Cognition and Behavior of Mammals

Abstract: Silver nanoparticles have been widely used in the lighting and food industries, in medicine, and in pharmaceutics as an antiseptic agent. Recent research demonstrates that, after prolonged oral administration, silver nanoparticles may cross the blood-brain barrier and accumulate in the brain in rather high amounts. In ex vivo experiments, it has also been shown that silver nanoparticles demonstrate neurotoxicity. The objective of this work was to answer the questions whether silver nanoparticles change cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 29 publications
(35 reference statements)
4
41
0
Order By: Relevance
“…Recently, Węsierska et al reported that oral gavage with a dose of 1 mg/kg of AgNPs produced adverse effect on memory and cognitive function [32]. In addition, Antsiferova et al investigated the effects of the prolonged oral administration of PVP-coated AgNPs at the dosage of 50 μg per day demonstrating impairment of long-term memory [33].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Węsierska et al reported that oral gavage with a dose of 1 mg/kg of AgNPs produced adverse effect on memory and cognitive function [32]. In addition, Antsiferova et al investigated the effects of the prolonged oral administration of PVP-coated AgNPs at the dosage of 50 μg per day demonstrating impairment of long-term memory [33].…”
Section: Introductionmentioning
confidence: 99%
“…Since the beginning of the 2000s, silver nanoparticles (Ag-NPs) have been used in various applications from pharmaceutics [ 1 , 2 , 3 , 4 ] to textiles [ 5 , 6 , 7 ] and from hygiene products [ 8 ] and packing materials [ 9 ] to daily food supplements [ 10 , 11 , 12 , 13 , 14 ]. Undoubtedly, Ag possesses unique antiseptic properties that have been known since antiquity [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…ER stress and UPR activate important proteins such as the inositol requiring protein 1 (IRE1), PKR-like endoplasmic reticulum kinase (PERK), and activating transcription factor-6 (ATF-6) which act as stress sensing proteins and are early markers for ER stress induced nanotoxicity [43]. Prolonged exposure of C57Bl/6 male mice to AgNPs causes contextual cognition and behavior anomalies in mammals [44]. Neurotoxicity induced by nanoparticles causes adverse effects on the structure, function or chemistry of the nervous system by increasing level of ROS, elevation of cytokines, and dysregulation of apoptosis leading to neuronal death [45,46].…”
Section: Introductionmentioning
confidence: 99%